加薪是萬靈丹？ 桃園市國民小學教師兼任行政職務意願影響因素建構之研究 Is Increasing Salary a Panacea? A Study on the Factors Influencing Taoyuan City Elementary School Teachers’ Willingness to Assume Administrative Roles - 黃鈺容 Yu-Jung Huang; 陳建志 Chien-Chih Chen (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2025)
本研究旨在探討桃園市國民小學教師選擇兼任行政職務的影響因素。相關研究指出透過提升行政加給或增加福利，或可提升教師擔任行政職務意願。然而，這是否能有效解決人力不足問題，仍有待深入探討。本研究以文獻回顧為基礎，再與兩位專家修正後，建立家庭因素、個人因素、組織因素與薪資酬賞因素四個構面及11個向度，並採用層級分析法 (Analytic Hierarchy Process, AHP) 分析權重比例，並輔以半結構式訪談。獲致結論如下：一、影響兼任行政職意願的四個構面中，「家庭因素」最重要，其次為「個人因素」；二、影響兼任行政職意願的首要個人因素為「人格特質」；三、影響兼任行政職意願的首要組織因素為「組織氣氛」；四、影響兼任行政職意願的首要薪資酬賞因素為「內在報酬」；五、影響兼任行政職務意願的首要家庭因素為「家庭支持」；六、不同背景變項對兼任行政職務意願因素的影響有所差異。本研究根據結論提出相關研究建議。 This study explores the factors influencing elementary school teachers in Taoyuan City to take on additional administrative roles. Relevant studies have suggested that increasing administrative stipends or offering additional benefits may enhance teachers’ willingness to assume such positions. However, whether these measures can effectively address the issue of insufficient administrative personnel requires further examination. Based on a comprehensive literature review and discussions with two experts, this study established four dimensions—family factors, personal factors, organizational factors, and compensation factors—along with 11 associated criteria. The analytic hierarchy process (AHP) was employed to analyze the weight ratios of these dimensions, supplemented by semi-structured interviews. 1. The study found that among the four dimensions influencing teachers’ willingness to take on administrative roles, “family factors” are the most significant, followed by “personal factors” ; 2. The primary personal factor influencing willingness is “personality traits” ; 3. The key organizational factor is “organizational climate” ; 4. The foremost compensation factor is “intrinsic rewards” ; 5. The main family factor is “family support” ; 6. And different background variables influence teachers’ willingness to assume administrative roles. The study proposes relevant recommendations based on these findings.